Improving the Management of an Advanced Extrauterine Pregnancy Using Pelvic Arteriography in a Hybrid Operating Suite - Michael P. Smrtka; Ravindu Gunatilake; Michael J. Miller; R. Phillips Heine; Haywood L. Brown (Thieme Medical Publishers, Inc., 2012)
Advanced extrauterine pregnancy is an extremely rare, life-threatening pregnancy complication. Management of these pregnancies presents significant challenges, especially when they have progressed to an advanced stage of fetal viability. With high rates of maternal and fetal mortality associated with this complication, delivery or pregnancy interruption should be expedited following diagnosis. Localization of the placenta and its blood supply is critical to preoperative planning. Hybrid operating suites that can accommodate a multidisciplinary team of subspecialists may improve the chance of a successful outcome with this rare complication.